2017
DOI: 10.3390/aerospace4030049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Radar and ADS-B Influences on Aircraft Detect and Avoid (DAA) Systems

Abstract: Detect and Avoid (DAA) systems are complex communication and locational technologies comprising multiple independent components. DAA technologies support communications between ground-based and space-based operations with aircraft. Both manned and unmanned aircraft systems (UAS) rely on DAA communication and location technologies for safe flight operations. We examined the occurrence and duration of communication losses between radar and automatic dependent surveillance-broadcast (ADS-B) systems with aircraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Although adequate performance standards were established for various surveillance equipment, to date the impacts of surveillance system failures in terms of separation degradation, specifically in the UAS platform, have not been defined. Moreover, traditional radar and Mode-A/C transponder technologies show inherent deficiencies in different airspace and equipage scenarios especially in the presence of high air traffic densities [25][26][27][28][29][30][31][32][33]. The failure modes for different cooperative sensors such as Mode S, TCAS, ADS-B are well defined and safety assessments have been carried out on the individual surveillance sensor considering functions in the manned aircraft.…”
Section: Detect and Avoid (Daa) Safety Assessmentmentioning
confidence: 99%
“…Although adequate performance standards were established for various surveillance equipment, to date the impacts of surveillance system failures in terms of separation degradation, specifically in the UAS platform, have not been defined. Moreover, traditional radar and Mode-A/C transponder technologies show inherent deficiencies in different airspace and equipage scenarios especially in the presence of high air traffic densities [25][26][27][28][29][30][31][32][33]. The failure modes for different cooperative sensors such as Mode S, TCAS, ADS-B are well defined and safety assessments have been carried out on the individual surveillance sensor considering functions in the manned aircraft.…”
Section: Detect and Avoid (Daa) Safety Assessmentmentioning
confidence: 99%
“…As the onboard computer will make use of surveillance sensor data to trigger alert in the absence of the 'human eye', it is crucial to have robust and efficient surveillance sensors. However, studies have shown that, both the 1090ES and UAT ADS-B are prone to significant message degradations [8][9][10][11][12][13][14][15][16]. One of the drawbacks of ADS-B is message loss or dropout.…”
Section: Introductionmentioning
confidence: 99%
“…One of the drawbacks of ADS-B is message loss or dropout. In our previous studies, ADS-B has shown significant message loss along with different message anomalies [13][14][15][16]. In this work, the severity and risk associated with ADS-B drop-out in DAA function are investigated utilizing Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Initial assessment of UAT ADS-B [5], [6], [7] showed significant message degradations. One of the anomalies of ADS-B is message discontinuation or drop out.…”
Section: Introductionmentioning
confidence: 99%
“…This work emphasizes the severity and risk associated with drop out in UAS DAA. The investigation is based on the extended ADS-B data analysis carried out at be Semke et el [6]. The analysis predicts how ADS-B message drop out could affect UAS DAA system if used as a single means of surveillance.…”
Section: Introductionmentioning
confidence: 99%